Early Blockade of CB1 Receptors Ameliorates Schizophrenia-like Alterations in the Neurodevelopmental MAM Model of Schizophrenia - Stark, Tibor; Iannotti, Fabio Arturo; Di Martino, Serena; Di Bartolomeo, Martina; Ruda-Kucerova, Jana; Piscitelli, Fabiana; Wotjak, Carsten T; D'Addario, Claudio; Drago, Filippo; Di Marzo, Vincenzo; Micale, Vincenzo (Biomolecules, 2022)
In agreement with the neurodevelopmental hypothesis of schizophrenia, prenatal exposure of Sprague-Dawley rats to the antimitotic agent methylazoxymethanol acetate (MAM) at gestational day 17 produces long-lasting behavioral alterations such as social withdrawal and cognitive impairment in adulthood, mimicking a schizophrenia-like phenotype. These abnormalities were preceded at neonatal age both by the delayed appearance of neonatal reflexes, an index of impaired brain maturation, and by higher 2-arachidonoylglycerol (2-AG) brain levels. Schizophrenia-like deficits were reversed by early treatment [from postnatal day (PND) 2 to PND 8] with the CB1 antagonist/inverse agonist AM251 (0.5 mg/kg/day). By contrast, early CB1 blockade affected the behavioral performance of control rats which was paralleled by enhanced 2-AG content in the prefrontal cortex (PFC). These results suggest that prenatal MAM insult leads to premorbid anomalies at neonatal age via altered tone of the endocannabinoid system, which may be considered as an early marker preceding the development of schizophrenia-like alterations in adulthood.
Keywords: Rats; schizofrenie; Female; zvířata; Rats, Sprague-Dawley; Animals; Pregnancy; potkani Sprague-Dawley; ženské pohlaví; krysa rodu Rattus; Receptor, Cannabinoid, CB1; Disease Models, Animal; Schizophrenia; methylazoxymethanolacetát; receptor kanabinoidní CB1; Methylazoxymethanol Acetate; těhotenství; modely nemocí na zvířatech